APLICAÇÃO DE ATIVADOR BIOLÓGICO EM CONSÓRCIO DE Urochloa decumbens COM MILHETO E EM CULTIVO SOLTEIRO - SANTANA, Dthenifer Cordeiro; MACHADO, Douglas Schlosser; AGUILAR, Gabriel de Santis Bertholini; AREVALO, Ana Caroline Mello; TORRES, Francisco Eduardo (ANAIS DO ENIC, 2018)
-